Role of oxide seed layer in plastic response of epitaxially grown textured metal films. (15th June 2016) - Das, Debashish; Power, Brian; Martin, Joel P.; Polcawich, Ronald G.; Chasiotis, Ioannis
Abstract: The elastic/plastic mechanical behavior of freestanding polycrystalline 111-textured Pt films with thicknesses 50–1000 nm and different combinations of grain size and film thickness, grown epitaxially on a 35–50 nm thick polycrystalline (100)-TiO2 (rutile) seed layer, was studied at uniaxial tension strain rates 10 −6 - 10 s −1 . The mismatch strain between the 111-Pt films and the underlying (100)-TiO2 seed layer gives rise to an interfacial dislocation network, which, in turn, determines the initiation of plastic deformation in Pt. Experiments showed that the flow stress increases, while the plastic strain accumulation at failure decreases with decreasing Pt film thickness. A modified Thompson model that accounted for the combined effect of film thickness and grain size provided good predictions for the elastic limit of Pt films. However, the yield stress was underestimated by the same model; a Taylor strain hardening model was superimposed to the modified Thompson model to account for additional hardening as a result of dislocation interactions during plastic deformation, which provided good predictions for the evolution of flow stress with plastic strain. Graphical abstract: